The interpretation and utilization of cultural heritage and its values by young people in Slovenia : is heritage really boring and uninteresting? - Fakin Bajec, Jasna (Array, 2019)
This paper analyses approaches to involving young people in the processes of valuation, interpretation and utilization of local heritage to meet contemporary development challenges. The starting point is the finding that European development strategies highlight the various potentials of cultural heritage, but young people from western Slovenia hardly see any of these potentials. Moreover, the presented ethnographic research results show that young people are not very interested in heritage practices undertaken in their cities or villages. This paper’s results demonstrate how heritage may be introduced to young generations, how youth understand local heritage and its values, and what they think about voluntary activities in cultural fields.